Identification of a Hexenal Reductase That Modulates the Composition of Green Leaf Volatiles. Issue 2 (20th August 2018) - Tanaka, Toshiyuki; Ikeda, Ayana; Shiojiri, Kaori; Ozawa, Rika; Shiki, Kazumi; Nagai-Kunihiro, Naoko; Fujita, Kenya; Sugimoto, Koichi; Yamato, Katsuyuki T.; Dohra, Hideo; Ohnishi, Toshiyuki; Koeduka, Takao; et al.
Abstract : NADPH-dependent cinnamaldehyde and hexenal reductase affects the composition of green leaf volatiles and is involved in indirect plant defenses. Abstract: Green leaf volatiles (GLVs), including six-carbon (C6) aldehydes, alcohols, and esters, are formed when plant tissues are damaged. GLVs play roles in direct plant defense at wound sites, indirect plant defense via the attraction of herbivore predators, and plant-plant communication. GLV components provoke distinctive responses in their target recipients; therefore, the control of GLV composition is important for plants to appropriately manage stress responses. The reduction of C6-aldehydes into C6-alcohols is a key step in the control of GLV composition and also is important to avoid a toxic buildup of C6-aldehydes. However, the molecular mechanisms behind C6-aldehyde reduction remain poorly understood. In this study, we purified an Arabidopsis ( Arabidopsis thaliana ) NADPH-dependent cinnamaldehyde and hexenal reductase encoded by At4g37980, named here CINNAMALDEHYDE AND HEXENAL REDUCTASE (CHR). CHR T-DNA knockout mutant plants displayed a normal growth phenotype; however, we observed significant suppression of C6-alcohol production following partial mechanical wounding or herbivore infestation. Our data also showed that the parasitic wasp Cotesia vestalis was more attracted to GLVs emitted from herbivore-infested wild-type plants compared with GLVs emitted from chr plants, which corresponded with reduced C6-alcohol levels in the mutant. Moreover, chr plants were more susceptible to exogenous high-dose exposure to ( Z )-3-hexenal, as indicated by their markedly lowered photosystem II activity. Our study shows that reductases play significant roles in changing GLV composition and, thus, are important in avoiding toxicity from volatile carbonyls and in the attraction of herbivore predators.